Hospital arrival time after onset of stroke. Issue 10 (October 1992) - Kay, R; Woo, J; Poon, W S
Abstract : To estimate the proportion of patients with stroke likely to be eligible for a trial of anticoagulant treatment for acute ischaemic stroke, the interval between onset of symptoms and arrival at hospital was analysed prospectively. Of 773 patients with stroke admitted in one year, 63% arrived at hospital within 12 hours, 76% within 24 hours, and 85% within 48 hours of ictus. The arrival time varied significantly with stroke subtype. Patients with intracerebral haemorrhage tended to arrive earlier than those with cerebral infarct, who arrived sooner than those with lacunar infarct. The results suggest that about half of all patients with ischaemic stroke in Hong Kong would present within 12 hours of ictus, in time for inclusion in a therapeutic trial.